IMMUNOHISTOCHEMICAL EXPRESSION OF ANDROGEN RECEPTOR IN TRIPLE NEGATIVE BREAST CARCINOMA AT ARMED FORCES INSTITUTE OF PATHOLOGY, RAWALPINDI - Ameer, Amna; Akhtar, Farhan; Ud Din, Hafeez; Ahmad, Rabia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of immunohistochemical expression of androgen receptor in triple negative breast carcinoma. Study Design: Cross sectional study. Duration and Place of Study: This study included 30 cases confirmed as triple negative breast carcinoma at Armed Forces Institute of Pathology Rawalpindi, from Jan to Jul 2018. Methodology: Anti-androgen receptor antibody was applied and assessed. Positive expression was defined as greater and equal to 10% nuclear immunostaining. SPSS-24 was used for analyzing data. Results: Out of 30 cases of triple negative breast carcinoma (TNBC), all patients were female. Patients’ ages ranged between 21-72 years with a mean age of 46.35 years and a standard deviation of ± 13.4. Androgen receptor expression was positive in 8 cases (27%) of all triple negative breast carcinomas. Out of these androgen receptor (AR) triple negative breast carcinomas; all 8 cases were of histological subtype invasive ductal (mammary) carcinoma, non special type, 7 cases (23%) were of histological grade 3 and 1 was of histological grade 2. Conclusion: Androgen receptor expression is observed in 8 cases (27%) of triple negative breast carcinoma cases. Such patients can be selected as candidates for anti- androgen receptor targeted therapy.